2018
DOI: 10.1021/jacs.8b01411
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Addition, Transmetalation, and Reductive Elimination at a 2,2′-Bipyridyl-Ligated Gold Center

Abstract: Three-coordinate bipyridyl complexes of gold, [(κ-bipy)Au(η-CH)][NTf], are readily accessed by direct reaction of 2,2'-bipyridine (bipy), or its derivatives, with the homoleptic gold ethylene complex [Au(CH)][NTf]. The cheap and readily available bipyridyl ligands facilitate oxidative addition of aryl iodides to the Au(I) center to give [(κ-bipy)Au(Ar)I][NTf], which undergo first aryl-zinc transmetalation and second C-C reductive elimination to produce biaryl products. The products of each distinct step have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
99
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 105 publications
(111 citation statements)
references
References 59 publications
11
99
0
1
Order By: Relevance
“…Significant recent progress has been made in demonstrating elementary cross‐coupling steps at Au centers . Bourissou, Amgoune, and co‐workers and our group have shown that Au I systems modified with appropriate ligands are effective for hitherto unknown Ar−X (X=I, Br) oxidative additions . In addition to these thermal pathways, significant progress has also been made in oxidative addition at gold using photochemically activated routes .…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Significant recent progress has been made in demonstrating elementary cross‐coupling steps at Au centers . Bourissou, Amgoune, and co‐workers and our group have shown that Au I systems modified with appropriate ligands are effective for hitherto unknown Ar−X (X=I, Br) oxidative additions . In addition to these thermal pathways, significant progress has also been made in oxidative addition at gold using photochemically activated routes .…”
Section: Methodsmentioning
confidence: 99%
“…Catalysts that can overcome this are significant because they dispense with the highly reactive external or internal oxidants typically required in Au‐mediated cross‐couplings. Indeed, using Ar−X oxidative addition as a platform, redox neutral Au‐based aryl C−H arylations and Negishi‐like cross‐couplings have now been achieved . In these studies, reversible Ar−X oxidative addition was faster for more electron rich arenes, offering a counterpoint to the electronic trends typically seen in Pd‐based processes .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations